Social Support and Well-Being: The Survival Kit for the Work Jungle - Mariana Oliveira; Ana Palma-Moreira; Manuel Au-Yong-Oliveira (Social Sciences)
This study aimed to investigate the effect of perceived social support on perceived employability and whether this relationship is mediated by well-being. Another objective is to study the moderating effect of perceived self-efficacy on the relationship between well-being and perceived employability. The sample comprises 316 participants, all studying at universities in Portugal. The results show that social support is positively and significantly associated with perceived employability and well-being. Well-being has a positive and significant association with perceived employability. As for the mediating effect, well-being was found to have a total mediating effect on the relationship between social support and perceived employability. Perceived self-efficacy has a positive and significant association with perceived employability. Contrary to expectations, perceived self-efficacy does not moderate the relationship between well-being and perceived employability. These results allow us to conclude that social support and well-being are the survival kits for the jungle of work. As for the practical implications, it is recommended that universities take care of the social support given to students, increasing their well-being so that their perceived employability is high.